RANCANG BANGUN MATIKLOPEDIA BERBASIS CHARACTER BUILDING DI SEKOLAH DASAR - Masduki, Lusi Rachmiazasi; Surtini, Sri (AKSIOMA, 2014)
This study aimed to develop the learning of mathematics with a medium term Matiklopedia which is based on character education for elementary school students. In accordance with these objectives, the type of study is a research development (educational research and development) by Plomp (1997) and modified Borg and Gall, which includes five phases: (1) initial research (preliminary phase investigation), (2) design (design phase), (3) realisaasi / construction (phase realization /construction), (4) testing, evaluation and revision, (phase test, evaluation & revition) and (5) implementation (implementation phase). In this first year has produced Matiklopedia the initial design has been validated by experts and media materials to the value of the matter experts with the percentage 90% are excellent and validation of media experts with a percentage score of 90% are excellent, but there was still construct validated by student SDN Tugurejo 01,02,03 Semarang. Key Word: Development, Matiklopedia, Character Education